Study of the Effect of Grafted Antioxidant on the Acrylonitrile-Butadiene Copolymer Properties - Abdulaziz Ibrahim Al-Ghonamy; Mirham A. Barakat (International Journal of Polymer Science)
The grafting of ADPEA onto natural rubber was executed with UV radiation. Benzoyl peroxide was used to initiate the free-radical grafting copolymerization. Natural rubber-graft-N-(4-aminodiphenylether) acrylamide (NR-g-ADPEA) was characterized with an IR technique. The paper aims interested to determine the crosslinking density by using the ultrasonic technique. The ultrasonic velocities of both longitudinal and shear waves were measured in thermoplastic discs of NBR vulcanizates as a function of aging time. Ultrasonic velocity measurements were taken at 2 MHz ultrasonic frequency using the pulse echo method. We studied the effect of aging on the mechanical properties, crosslinking density, and the swelling and extraction phenomena for acrylonitrile-butadiene copolymer (NBR) vulcanizates, which contained the prepared NR-g-ADPEA and a commercial antioxidant, N-isopropyl-𝑁−-phenyl-p-phenylenediamine. The prepared antioxidant enhanced both the mechanical properties of the NBR vulcanizates and the permanence of the ingredients in these vulcanizates.